Comparative study of SGS models for simulating the flow in a centrifugal-pump impeller using single passage. Issue 7 (5th October 2015) - Huang, Xianbei; Liu, Zhuqing; Yang, Wei
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to bring in and clarify the performance of the Vreman and dynamic Vreman models (VM and DVM) in simulating the internal flow of the centrifugal pump impeller. Design/methodology/approach – Four subgrid scale (SGS) models, including the Smagorinsky model, the dynamic Smagorinsky model, the VM and the DVM are chosen to study the performance in predicting the flow field in the centrifugal pump impeller at design load. The velocity and turbulent kinetic energy distributions are compared. Also, the temporal variation of the model coefficient of the DVM is studied. Findings – The results of all the four models show agreement with both the PIV and LDV data. It is clarified that the VM and the DVM are adaptive in simulating the turbulent flow in the centrifugal pump at design load, and the DVM shows even better performance in predicting the velocity distribution. Additionally, the temporal variation of the model coefficient of the DVM is about 0.01, which is the optimal value for VM in this study. It is verified that VM can perform as good as the dynamic models when an appropriate model coefficient is chosen. Originality/value – The applicability of the VM and the DVM in simulating the internal flow of the centrifugal pump has been proven at design load. The introducing of the two models into centrifugal pump's simulation can provide some new ideas in constructing more adaptive SGS models for this kind of high-rotating flow.